Mineralogical Marvels: Deciphering the Geological Alchemy from Stones to Wealth - Gheit, Amer A (Journal for Research in Applied Sciences and Biotechnology, 2022)
This research endeavors to dissect the mineralogical intricacies governing the alchemical metamorphosis of geological substrates into economic wealth. Employing a multifaceted approach, this study scrutinizes the crystallographic and chemical underpinnings of economically consequential minerals. Crystallographically, an exploration of intricate structures elucidates the nexus between crystal lattice configurations and resultant mineral properties, instrumental in ascertaining economic worth. Concurrently, an in-depth chemical analysis discerns the elemental intricacies dictating mineral value, establishing a nexus between compositional intricacies and economic significance. The investigation extends to the geological crucible where ore formation processes and diverse geological settings are analyzed. This includes an examination of the dynamic interplay of factors engendering the concentration of economically salient minerals. Consequently, this study accentuates the geological environments fostering mineral richness and includes pertinent case studies. Furthermore, an economic trajectory is traced, covering extraction, processing methodologies, and market dynamics. This encompasses an appraisal of contemporary mining and processing technologies, along with a discerning scrutiny of the geopolitical intricacies steering global mineral markets. In conclusion, this research amalgamates its findings into a cohesive narrative, presenting a nuanced understanding of the geological genesis of mineral wealth and its implications for scientific and economic paradigms.